2011
DOI: 10.4081/ejh.2011.e2
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of neurotransmission in the developing rat cochlea: immunohistochemical evidence from differential expression of synaptophysin and synaptobrevin 2

Abstract: Synaptophysin and synaptobrevin 2 associate closely with packaging and storage of synaptic vesicles and transmitter release, and both play important roles in the development of rat cochlea. We examined the differential expression of synaptophysin and synaptobrevin 2 in the developing Sprague-Dawley rat cochlea, and investigated the relationship between their expression and auditory development. The expression of synaptophysin and synaptobrevin 2 was not observed in Kolliker's and Corti's organ at postnatal 1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…In the present study, hair cell-like cells adjacent to SGNs showed presynaptic punctate expression of CtBP2. Expression of SYP, a membrane protein specific to synaptic vesicles, correlates directly with the presence of neurotransmitter [ 49 ]. Expression of SYP was detected at the nerve endings of SGNs adjoining hair cell-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, hair cell-like cells adjacent to SGNs showed presynaptic punctate expression of CtBP2. Expression of SYP, a membrane protein specific to synaptic vesicles, correlates directly with the presence of neurotransmitter [ 49 ]. Expression of SYP was detected at the nerve endings of SGNs adjoining hair cell-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining was conducted as described previously (45), modified to some extent. Another half of mice in each group were deeply anesthetized with 4% isoflurane.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…The expression of specific protein marker was assessed during pre- and post-natal development in mammalian species, 52 - 65 starting from the process of oocytes maturation and elimination. 55 , 56 , 61 , 62 The development of heart and skeletal muscle was the subject of several papers, where special attention was paid to stem cell populations and their molecular characteristics.…”
Section: Histochemistry and Cytochemistry In Recent Literaturementioning
confidence: 99%